Bank Competition, Banking Cost, Banking Market, Economies of Scale: Exploring the dynamics of competition in the banking sector (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Competition in banking is entirely different from other sectors of the economy due to the special function of banks in the financial system. The standard competition paradigm in favour of competition regarding cost minimization and allocative efficiency is not entirely valid for banking because many market failures distort the nature of competition and its outcomes. The uniqueness and fragility of banks, business models in banking and competition paradigm in banking is discussed. Finally, the different reviews of competition frequently used in the empirical literature on banking are studied.